A systematic mapping study on mobility mechanisms for cloud service provisioning in mobile cloud ecosystems. (July 2018) - Junior, Warley; Silva, Bruno; Dias, Kelvin
Abstract: Hand-over is a critical issue with regard to Mobile Cloud Computing (MCC) infrastructure, notably as it impacts applications' quality of service due to hardware constraints of the device, which can result in low connectivity in a wireless environment. Over the last couple of years, several research efforts have been targeted at supporting mobility mechanisms development and adapting existing technologies for the mobile cloud environment. The goal of this paper is to use a Systematic Mapping Study (SMS) method for identifying and analyzing mobility mechanisms in the MCC context. Our review comprised the following contributions: (i) characterizing existing research by considering six facets: overall purpose, network technology, decision parameter, mobile application, cloud model, and mobility strategy; (ii) producing a spreadsheet with information about each paper in the screening and extraction processes; and (iii) systematically mapping the solutions to determine research gaps and trends.